Protocol of testing the feasibility and acceptability of two brief dyadic sleep interventions for adults with cancer and their bedpartner caregivers - Youngmee Kim; Thomas C. Tsai; Jennifer L. Steel; Alberto R. Ramos; Jean-Philippe Laurenceau; Wendy M. Troxel (Pilot and Feasibility Studies)
Abstract Background Sleep disturbance is common and problematic among both patients with cancer and their bedpartner caregivers. Although one’s sleep affects the partner’s sleep, existing cognitive-behavioral interventions have rarely targeted sleep problems of patients and caregivers simultaneously. Methods This protocol is to test the feasibility and acceptability of two brief dyadic sleep interventions [My Sleep Our Sleep (MSOS) and Brief Behavioral Treatment for Insomnia for Couples with Cancer (BBTI-CC)] that are designed to reduce sleep disturbance and improve health-related quality of life in adults with cancer and their bedpartner caregivers. Participants (patient-caregiver dyads) will be randomly assigned to either intervention condition. Both interventions will be delivered weekly for 4 weeks. Questionnaire, daily sleep logs, and objectively assessed sleep data will be collected before the intervention (T1), 1-week (T2) and 8-week (T3) after conclusion of the intervention. Participant-reported satisfaction with the intervention will be assessed at the end of each of the four intervention sessions. Discussion We estimate 50 dyads will be enrolled (50 patients and 50 caregivers; 25 dyads in each intervention condition). In both conditions, we expect > 75% of eligible and screened dyads will consent to participate within the enrollment period, > 80% of enrolled dyads will complete the intervention, and > 80% of participants will report satisfaction across all acceptability measures. Additionally, we will explore if both MSOS and BBTI-CC reveal a similar effect on overall sleep disturbance, insomnia severity, and health-related quality of life. Results will inform the feasibility and acceptability of conducting brief dyadic sleep interventions and provide preliminary data to guide further refinement of intervention content and procedure for adult patients with cancer and their bedpartner caregivers in a full trial. Trial registration NCT06569693 Clinicaltrials.gov, registered August 22 2024, https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S000ESX9&selectaction=Edit&uid=U0005GPT&ts=2&cx=nb0aq5 .